A multichannel amplitude and relative-phase controller for active sound quality control. (1st May 2017) - Mosquera-Sánchez, Jaime A.; Desmet, Wim; de Oliveira, Leopoldo P.R.
Abstract: The enhancement of the sound quality of periodic disturbances for a number of listeners within an enclosure often confronts difficulties given by cross-channel interferences, which arise from simultaneously profiling the primary sound at each error sensor. These interferences may deteriorate the original sound among each listener, which is an unacceptable result from the point of view of sound quality control. In this paper we provide experimental evidence on controlling both amplitude and relative-phase functions of stationary complex primary sounds for a number of listeners within a cavity, attaining amplifications of twice the original value, reductions on the order of 70 dB, and relative-phase shifts between ± π rad, still in a free-of-interference control scenario. To accomplish such burdensome control targets, we have designed a multichannel active sound profiling scheme that bases its operation on exchanging time-domain control signals among the control units during uptime. Provided the real parts of the eigenvalues of persistently excited control matrices are positive, the proposed multichannel array is able to counterbalance cross-channel interferences, while attaining demanding control targets. Moreover, regularization of unstable control matrices is not seen to prevent the proposed array to provide free-of-interference amplitude and relative-phase control, but the system performance is degraded, as a function of the amount of regularization needed. The assessment of Loudness and Roughness metrics on the controlled primary sound proves that the proposed distributed control scheme noticeably outperforms current techniques, since active amplitude- and/or relative-phase-based enhancement of the auditory qualities of a primary sound no longer implies in causing interferences among different positions. In this regard, experimental results also confirm the effectiveness of the proposed scheme on stably enhancing the sound qualities of periodic sounds for multiple listeners within a cavity. Abstract : Highlights: A multichannel algorithm that deals with cross-channel interferences is proposed. Amplitude and relative-phase of complex sounds are independently controlled. Experiments in a small cavity verify attainment of burdensome control targets. Sound quality is independently enhanced for several listeners within an enclosure.